Commons, property law and management: A bibliometric study - Machado, Nélida Reis Caseca; Pereira, José Roberto (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
In this bibliometric review, with data from the Web Of Science (WOS), the main characteristics of scientific articles published in international journals on Common Goods, Property Law and Management are specified. The result returned 146 works and it was analyzed in 12 categories: temporal evolution of scientific production; temporal evolution of the number of article citations; production by countries; production by networked countries; categories of publications; association between authors and categories, most cited works; citation network; clusters by title; top citations in the category Government and Law, publications in Brazil. There is a growing interest of the scientific community in the matter and from this study other may arise.